Sucker Punch - Hamilton, Laurell K. (New York : Berkley, 2020)
"A brutal murder, a suspect in jail, and an execution planned, but what if the wrong person is about to be executed? When a fellow U.S. Marshal asks Anita Blake to fly to a tiny community in Michigans Upper Peninsula on an emergency consult, she knows time is running short. When she gets there, there is plenty of proof that a young wereleopard killed his uncle in the most gruesome and bloodiest way possible. As the mounting evidence points to him, a warrant of execution is already under way. But something seems off about the murder, and Anita has been asked to examine the crime scene and the evidence for her expert opinion. Despite the escalating pressure from local cops and the familys cries for justice for their dead patriarch, Anita quickly realizes that the evidence doesnt quite add up. But with a tight-knit community up in arms and fear against supernaturals growing, time is almost up, as Anita races to uncover the truth and determine whether the Marshals have caught the killer or are about to execute an innocent man, all in the name of justice."--
Keywords: Blake, Anita (Fictitious character) -- Fiction; Vampires -- Fiction; Murder -- Investigation; Fiction; Shapeshifting -- Fiction; Paranormal fiction; Fantasy fiction; Thrillers (Fiction)